Laissez-Faire or Government Control: A Problem for John Wesley - Kingdon, Robert McCune (Church history, 1957)
Many students of John Wesley have examined his economic ideas;2 few have appreciated their range. At least three sources molded the economic thought of the founder of Methodism. Only one of them, the Christian ethical tradition, has been studied with sufficient care. It was, to be sure, the first and most prominent source. But it was followed, first by Wesley's reaction to certain acute social problems which forced themselves on his attention during the 1770's, then by the thought of one of the most prominent economists of that day, the Rev. Josiah Tucker, Dean of Gloucester. These later stimuli led Wesley to consider a problem which disturbed many of his contemporaries, the problem of the extent to which a government should be allowed to control commerce and industry. His thinking on this problem is important, not because of its sophistication, but because of the tremendous influence Wesley exerted on public opinion, through his uncommonly effective preaching, organizing, and writing.